Public debt stability in the People Republic of China rethinking the domar condition and its bond market application. - Yoshino, Naoyuki; Terada-Hagiwara, Akiko; Miyamoto, Hiroaki (East Asia working papers., 2021)
The authors find that public debt sustainability depends on the sensitivity of interest rates to changes in government bond supply and demand. This is true in the case of the People Republic of China, Greece, and Japan. This modified fiscal sustainability condition suggests that the opening of capital markets to nonresident investors is important together with stability of the bond market.